Pulp and paper made from selected aquatic macrophytes using Western and Japanese methods - Hamzah, Zarith Sofia (2013)
Six (6) species of aquatic macrophytes; Pandanus odoratissimus, Nypa fruticans, Cyperus compressus, Fimbristylis miliacea, Rhyncospora corymbosa and Monochoria hastata were selected to determine their suitability for raw material of pulp in papermaking using Western and Japanese methods. The macrophytes were examined for their fiber dimension and derived value. Pandanus odoratissimus was the most suitable aquatic macrophytes for raw material in papermaking based on the highest fiber length (1.49±0.04 mm), fiber lumen (5.52±0.24μm) and cell wall thickness (3.69±0.17μm). All the species were suitable for papermaking with slenderness ratio >60. Based on chemical composition, Monochoria hastata stem was suitable species for paper pulp with the highest value of cellulose (72.54±10.41) and <30% of lignin (22.63±7.42). Five speciesof macrophytes were used to produced paper using Western method but only two species were used to make paper using Western and Japanese methods. Paper produced from Monochoria hastata using Western method showed the highest breaking length which was 2377.80±0.33 m while paper from Rhyncospora corymbosa using Japanese method showed highest tensile strength which was 3.78±0.71 kN/m. The selected aquatic macrophytes in this present study suitable for papermaking using both Western and Japanese methods to produced moderate quality of paper.